Catalytic Enantioselective Synthesis of α‐Substituted Secondary Allylic Alcohols from Terminal Alkynes and Aldehydes via Vinylaluminum Reagents. Issue 52 (14th November 2013) - Kumar, Ravindra; Kawasaki, Hiroki; Harada, Toshiro
<x xml:space="preserve">Abstract</x> One‐pot procedure: A general method for the highly enantioselective synthesis of α‐substituted allylic alcohols has been developed starting from readily available terminal alkynes and aldehydes and proceeding via vinylaluminum reagents (see scheme, dppp=1, 3‐bis(diphenylphosphino)propane). The use of Me2AlH is essential in the Ni‐catalyzed hydroalumination step to generate vinylaluminum reagents that cannot reduce the aldehyde.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>